Recurrence of spinal schwannoma: Is it preventable? - Senapati, Satya; Mishra, Sudhansu; Dhir, Manmath; Patnaik, Ashis; Panigrahi, Souvagya (Asian Journal of Neurosurgery, 2016)
Spinal schwannomas account for about 25% of primary intradural spinal cord tumors in adult. The prognosis for spinal schwannomas is excellent in most cases. Complete resection is curative. However following subtotal removal, recurrence develops after several years. We describe a case of recurrent spinal schwannoma who had been operated twice before for same disease. The possible cause of recurrence and difficulties in reoperation are discussed.
Keywords: Recurrent; spinal; schwannoma